Transcriptional regulation of the mouse gonadotropin-releasing hormone receptor gene in pituitary gonadotrope cell lines - Sadie, Hanél (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2006.